IV.4. Photographs of Marian Keaney, friends and landmarks, - Keaney, Marian, photographer (1974)
MS 49,553 /40 Folder 1: Photographs of Marian Keaney and friends including Thomas Pakenham, John Rebb, John Treacy, Denis Sharkey, Leo Daly, May Raleigh, Michael Casey and Josie McDermott.